Interleukin 17 Promotes Expression of Alarmins S100A8 and S100A9 During the Inflammatory Response of Keratinocytes - Christmann, Carolin; Zenker, Stefanie; Martens, Leonie; Hübner, Janina; Loser, Karin; Vogl, Thomas; Roth, Johannes (Frontiers in Immunology, 2021)
Psoriasis is one of the most common immune-mediated inflammatory diseases of the skin. Expression and secretion of two pro-inflammatory molecules of the S100-alarmin family, S100A8 and S100A9, in keratinocytes is a hallmark of psoriasis, which is also characterized by a disturbance of keratinocyte differentiation. Dimers of S100A8/S100A9 (calprotectin) bind to Toll-like receptor 4 and induce an inflammatory response in target cells. Targeted deletion of S100A9 reduced the inflammatory phenotype of psoriasis-like inflammation in mice. A role of S100-alarmins in differentiation and activation of keratinocytes has been suggested but has been never shown in primary keratinocytes. We now confirm that induction of S100-alarmins in an imiquimod-induced murine model of psoriasis-like skin inflammation was associated with an increased expression of interleukin (IL)-1α, IL-6, IL-17A or TNFα. This association was confirmed in transcriptome data obtained from controls, lesional and non-lesional skin of psoriasis patients and a down-regulation of S100-alarmin expression after IL-17 directed therapy. However, analyzing primary S100A9-/- keratinocytes we found that expression of S100A8/S100A9 has no significant role for the differentiation and inflammatory response pattern of keratinocytes. Moreover, keratinocytes are no major target cells for the extracellular pro-inflammatory effects of S100A8/S100A9 compared to stimulation with IL-1, IL-17A, IL-17F, or TNF. However, all these cytokines, especially IL-17A and F, highly abundant in psoriasis, strongly induced expression of S100-alarmins preferentially during early differentiation of keratinocytes. Our data indicates that expression of S100A8 and S100A9 does not primarily influence differentiation or inflammatory activation of keratinocytes but represents an amplifier of the dermal innate immune response.